A systems level approach to study metabolic networks in prokaryotes with the aromatic amino acid biosynthesis pathway - V. K, Priya; Sinha, Somdatta (Frontiers in Genetics, 2023)
Metabolism of an organism underlies its phenotype, which depends on many factors, such asthe genetic makeup, habitat, and stresses to which it is exposed. This is particularly importantfor the prokaryotes, which undergo significant vertical and horizontal gene transfers. In thisstudy we have used the energy-intensive Aromatic Amino Acid (Tryptophan, Tyrosine andPhenylalanine, TTP) biosynthesis pathway, in a large number of prokaryotes, as a modelsystem to query the different levels of organization of metabolism in the whole intracellular biochemical network, and to understand howperturbations, such as mutations, affects the metabolic flux through the pathway - in isolation and in the context of other pathways connected to it. Using an agglomerative approach involving complex network analysis and Flux Balance Analyses (FBA), of the TTP and other pathways connected to it, we identify several novel results. Using thereaction network analysis and FBA of the TTP and the genome-scale reconstructed metabolicpathways, many common hubs between the connected networks and the whole genomenetwork are identified. The results show that the connected pathway network can act as a proxy for thewhole genome networkin Prokaryotes. This systems level analysis alsopoints towards designing functional smaller synthetic pathways based on the reaction networkand FBA analysis.